Geschichtsraum Österreich Die Habsburger und ihre Geschichte in der bildenden Kunst des 19. Jahrhunderts - Telesko, Werner (2006)
The history is intended as the first comprehensive examination of the role of Austrian history in the visual arts of the Habsburg monarchy between 1804 and 1918. At its centre are the following three key questions: What status did the general preoccupation with history acquire? What where the favorite historical subjects for artistic representation? What significance did the Habsburgs´own history (almost endlessly "extendible" all the way back to its fictitious mythical beginnings) hold for the issues of the day? Works of art contribute to the creation of traditions in a double sense: a given work simultaneously contains and creates history. A work of art is also a medium for social identification, facilitating communication between the monarch and the people. Investigating the characteristics of the different "reflections on history" in the visual arts in Austria in the 19th century led to the practical necessity of significantly widening the known material basis. It became apparent that previous research was based on a relatively limited range of works (primarily "high art") and failed to relate these works to literary documents from the fiields of historiography or belles-lettres. I believe it is only by expanding the basis in terms of both word and picture documentation that a reliable overview of the different strategies pursued by Habsburg iconography can be gained. Not only did my chosen methodology seem expedient, and indeed almost indispensable for an examination of concrete historical cases, it also reveals that this interlocking approach (furthermore justified by the nature of the material) based on interrelating picture and text media contains the very key to a proper investigation of the historical art of the 19th century. In approaching the central questions, this study begins with an introduction that looks at concepts and methodology and charts the difficult formation of the "Austrian nation" from "Casa d´Austria" to the Habsburg "nation state". The second chapter examines the relevance of the Austrian 18th century in the consciousness of the following century based on the examples of rulers Maria Theresia and Joseph II. This is folloewd almost of necessity by a long section on the ruler iconography of the period Emperor Franz II (I) to Emperor Franz Joseph I. The visual strategies of the Habsburg rulers in the 19th century and the inseparable question of the legitimation of the Austrian Empire in the years after 1848 steer attention back to the quest for "origins" and to the Habsburg "insurance policy" of evoking the figure of founding father Rudolf I. This forms the main focus of the fourth chapter. In this context, the various appeals to the famous progenitor assume the character of an "underpinning" myth (Jan Assmann). The final chapter attempts to provide answers to questions relating to the "flowering" of Austrian historiography in the 19th century relative to historical interpretations in painting. The complex genesis of the celebration of glorious Austrian deeds ist examined on the basis of the concrete example of "military iconography" and the decoration of the "hall of fame" in the "Arsenal" in Vienna.